El diseño del centro político en Menorca como proyecto de construcción democrática. 1975-1977 - Sánchez Socías, Beatriz (Espacio Tiempo y Forma. Serie V, Historia Contemporánea, 2022)
This article analyses the creation of Unión de Centro Democrático (UCD) on the island of Menorca from Franco’s death until the configuration of the political parties shortly before the 1977 elections. Through documents from local and private archives, the press of the time and the testimonies of different political protagonists of the Menorcan process, the construction of a political formation that became the majority party in this constituency and in the whole of Spain is studied. In the case of Menorca, it is concluded that the centrists’ action was particularly important due to their leadership in promoting the articulation of Balearic pre-autonomy, which was assumed on the island as something inseparably linked to the achievement of democracy. This common goal of self-government gave rise to a unanimous consensus among all ideological sectors, from the conservative centre to the most progressive left, so that it was the Menorcan political elite that began to set the guidelines in the Balearic archipelago on pre-autonomy institutionalization, led by the UCD of Menorca.